2016
DOI: 10.1016/j.vetmic.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Wild boars harboring porcine epidemic diarrhea virus (PEDV) may play an important role as a PEDV reservoir

Abstract: Porcine epidemic diarrhea virus (PEDV) is a burdensome pathogen in the swine industry. Wild boar population poses a high risk for reservoir of viral pathogen. Two hundred eighty seven samples from wild boar (Sus scrofa) collected in South Korea during 2010/11 were analyzed using RT-PCR, revealing a PEDV infection rate of 9.75% (28/287). PEDV positive samples were distributed throughout the mainland of South Korea, clustering at the northern border adjacent to the Demilitarized Zone (DMZ) and in mountainous reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
(31 reference statements)
1
17
0
1
Order By: Relevance
“…Additionally, PEDV infects cells from pigs, humans, monkeys, duck, and bats, further supporting the theory that PEDV had crossed the batswine interspecies barrier sometime in the past (Table 1) [48,49]. PEDV has been detected from feral pigs in Korea and the US [50,51 ], with the latter study suggesting that PEDV may have spilled over from domestic to feral pigs. However, because there are no control measures to prevent PEDV circulation in feral pigs, they may represent a PEDV reservoir that can lead to PEDV outbreaks in the future.…”
Section: Origin and Potential For Intra/interspecies Transmissionsupporting
confidence: 54%
“…Additionally, PEDV infects cells from pigs, humans, monkeys, duck, and bats, further supporting the theory that PEDV had crossed the batswine interspecies barrier sometime in the past (Table 1) [48,49]. PEDV has been detected from feral pigs in Korea and the US [50,51 ], with the latter study suggesting that PEDV may have spilled over from domestic to feral pigs. However, because there are no control measures to prevent PEDV circulation in feral pigs, they may represent a PEDV reservoir that can lead to PEDV outbreaks in the future.…”
Section: Origin and Potential For Intra/interspecies Transmissionsupporting
confidence: 54%
“…Commissioned by the Dutch government, GD Animal Health was also monitoring wild boars for Aujeszky's disease, SVD, foot and mouth disease, CSFV, Trichinellosis and African swine fever. Because it is suggested that wild boars may play an important role as a PEDV reservoir (Lee et al, 2016), blood samples of wild boar collected as part of this monitor were also tested. These blood samples were collected from regions close to the borders with Germany and Belgium, from April till August 2014.…”
Section: Collection and Storage Of Samplesmentioning
confidence: 99%
“…Although opportunities for direct contact between feral swine and pigs in biosecure swine operations are limited, interactions have been documented with smaller backyard operations, and a recent multistate brucellosis outbreak was linked to backyard pigs infected by feral swine ( 5 ). Disease spillover into nondomestic hosts can serve as a continuous source for reintroduction into domestic animals, complicating international trade ( 6 ).…”
mentioning
confidence: 99%
“…Seventy-six feral swine sampled from the same island after that date were seronegative, suggesting that either seroprevalence was low enough to evade detection or that viral transmission burned out, most likely after initial deaths of susceptible piglets. Research in Asia, however, has found higher PEDV exposure in wild boar, reinforcing that animals can survive infection and raising the possibility of continual transmission in nondomestic swine populations ( 6 ).…”
mentioning
confidence: 99%